In situ macromolecular crystallography using microbeams - Axford, D; Owen, R; Aishima, J; Foadi, J; Stuart, D; Evans, G; Moraes, I; Morgan, A; Robinson, J; Nettleship, J; Owens, R; Fry, E; et al. (2012)
Despite significant progress in high-throughput methods in macromolecular crystallography, the production of diffraction-quality crystals remains a major bottleneck. By recording diffraction in situ from crystals in their crystallization plates at room temperature, a number of problems associated with crystal handling and cryoprotection can be side-stepped. Using a dedicated goniometer installed on the microfocus macromolecular crystallography beamline I24 at Diamond Light Source, crystals have been studied in situ with an intense and flexible microfocus beam, allowing weakly diffracting samples to be assessed without a manual crystal-handling step but with good signal to noise, despite the background scatter from the plate. A number of case studies are reported: the structure solution of bovine enterovirus 2, crystallization screening of membrane proteins and complexes, and structure solution from crystallization hits produced via a high-throughput pipeline. These demonstrate the potential for in situ data collection and structure solution with microbeams. © 2012 International Union of Crystallography Printed in Singapore - all rights reserved.